A Development of Optimization Model for Construction Site Layout Planning Using Genetic Algorithm - Duong, Chakrey; Peansupap, Vachara (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 28, 2023)
An effective construction site layout planning (CSPL) is essential to ensure site safety and enhance work efficiency. The primary task of CSPL process is to identify suitable location for temporary facilities (TFs) so that the safety and work efficiency can be improved. The problem of CSLP is generally formulated as an optimization problem, where a specific objective can be achieved with a set of constraints. Dealing with a large number of facilities, multiple tower cranes, and additional constraints can make the problem particularly challenging. In this study, a model is proposed to solve the problem of CSLP using Genetic Algorithm (GA). The model searches all free areas by using grid system to minimize the bias for facility location. In addition, the model can layout the location for tower cranes optimally. Flexibility of the model is increased by optimizing not only location for TFs, but also location for tower cranes. Moreover, this study investigated the effectiveness of closeness relationships on the developed model. A novel prototype was developed and tested to evaluate efficiency of the model. The results indicate that the proposed model can efficiently optimize the site layout for building projects. It can assist project managers in arranging facilities and tower cranes more effectively.